TEORI DAN PENDEKATAN PENDIDIKAN MULTIKULTURAL - Lusia Kristina Loke; Maria Dua Marung; Elviana Pona Rato (LPPM Universitas Muhammadiyah Bulukumba, 2023)
Abstract: The research aims to determine the theory and approach to milticultural education. Multicultural education is something that is very necessary in dealing with pluralistic conflicts originating from ethnic, cultural, tribal and religious diversity. Multicultural education is a response to the religious development of the school population, as well as demands for equal rights for each group. To implement this, the role of educators is very necessary because they can help instill life values ​​so that they can form characters that reflect national identity. This can be implemented in schools through (1) building an inclusive diversity paradigm in the school environment, (2) respecting linguistic diversity in schools, (3) building gender sensitive attitudes in schools, (4) building critical understanding and empathy for injustice and social differences, (5) building anti-discrimination attitudes ethnicity, (6) respecting differences in abilities, and, (7) respecting age differences. What must continue to be developed is multicultural education as a field of study so that when a global revolution occurs, this multicultural approach will remain relevant.